Kształtowanie obrazu miasta. Rola prawa i mechanizmów ekonomicznych = Role of law and economic mechanisms in the formation of the image of a town - Skiba, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In modern towns their image and identity are being formed in a more and more active way. Town authorities promote events, slogans, logos, which identify a town with actions and events. A clear image of a town can be i.e.: Bielawa ? a model ecological town, Cycling Śrem, Poddębice - a sunny town, Raciechowice - an ecological administrative commune.
Keywords: obraz miasta; rozwój miasta; oszczędność energetyczna; image of the city; city development; energy saving